Diagnostic accuracy of ultrasound in predicting birth‐weight discordance in twin pregnancy: systematic review and meta‐analysis. (3rd October 2017) - Leombroni, M.; Liberati, M.; Fanfani, F.; Pagani, G.; Familiari, A.; Buca, D.; Manzoli, L.; Scambia, G.; Rizzo, G.; D'Antonio, F.
ABSTRACT: Objective: To investigate the diagnostic performance of ultrasound in predicting birth‐weight (BW) discordance in twin pregnancy. Methods: Electronic databases PubMed, EMBASE and CINAHL were searched using combinations of MeSH terms 'birth weight', 'discordance', 'twins' and 'ultrasound'. Summary estimates of sensitivity, specificity, positive and negative likelihood ratios and diagnostic odds ratios for the predictive accuracy of sonographically estimated fetal‐weight (EFW) discordance and abdominal‐circumference (AC) discordance in predicting BW discordance were computed using hierarchical summary receiver–operating characteristics curves. Results: Twenty studies (including 5826 twin pregnancies) were included. EFW discordance ≥ 20% had a sensitivity of 65.4% and specificity of 90.8% in predicting BW discordance ≥ 20%. The predictive performance of ultrasound performed within 1 month, 2 weeks and 3 days before birth was 61.4%, 72.3% and 78.9%, respectively. EFW discordance ≥ 25% had a sensitivity of 57.7% and specificity of 95.2% in predicting BW discordance ≥ 25%. The sensitivity of EFW discordance ≥ 25% detected within 1 month, 2 weeks and 3 days before birth was 60.0%, 75.0% and 60.3%, respectively, while the corresponding values for specificity were 97.7%, 96.2% and 87.3%, respectively. In view of the different cut‐offs reported among studies, it was not possible to perform comprehensive data synthesis for each AC discordance cut‐off. The optimal diagnostic performance of AC discordance was for prediction of BW discordance ≥ 25%, with a sensitivity of 70.8% and specificity of 86.4%. Conclusion: Ultrasound EFW discordance has an overall moderate accuracy in predicting BW discordance in twin pregnancy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.